Analisis parameter biologis (kelimpahan plankton, bod) pada budidaya udang windu (Penaeus monodon) bersama rumput laut (Gracillaria sp.) dan kerang hijau (Perna sp.) dengan sistem imta (Integrated Multitrophic Aquaculture) - Rarin Silma Isnaini; Sri Rejeki; Tita Elfitasari (Departemen Akuakultur FPIK UNDIP, 2021)
Integrated Multi-throphic Aquaculture (IMTA) is a system in cultivation that prioritizes balance in its maintenance. The IMTA system is a cultivation method that utilizes feed residues that can be utilized by organism from the remaining feed biota at higher levels of trophic can be utilized by biota with lower trophic levels. This study aims to analyze the biological parameters with different densities of seaweed and green mussels and the best stocking densities for the growth and survival of tiger shrimp. The test animals used were PL 30 tiger shrimp with a range of sizes from 0.03 to 0.08 grams / larvae. Stocking density of tiger shrimp is 80 larvae / m2. The method used is the experimental method and complete randomized design with factorial design design with 9 treatments and 4 replications. The seaweed stock density treatment is 50, 100 and 150 grams while the stock of green seaweed stock is 30, 60, and 90 grams. The results showed that the highest growth rate and survival rate was found in treatment A1B1 with 50 grams of seaweed stocking density and 30 grams of green mussel with RGR value of 67.11% / day and the best SR of 88.75%. Phytoplankton found included 2 classes, namely Bacillariophyceae, and Cyanophyceae. Phytoplankton which dominates each treatment is found in the Bacillariophyceae class. The highest plankton abundance is found in A1B1 treatment with 50 grams of seaweed stock density and 30 grams of green mussels. BOD values in each treatment ranged from 4.5 to 7.1 mg /l.